Niedookreślenie teorii przez dane empiryczne a rewolucja relatywistyczna w fizyce - Sady, Wojciech (Filozofia Nauki, 2017)
Quine (1951) argued that, in the face of empirical anomalies, a given theoretical system can be modified in many different ways: “Any statement can be held true come what may, if we make drastic enough adjustments elsewhere in the system. […] Conversely, by the same token, no statement is immune to revision”. I will show that the history of relativistic revolution contradicts Quine’s claim. Indeed, when physicists tried to explain anomalous results of experiments from Arago (1810) to Michelson (1881-1887) — in which the influence of the motion of the Earth on the course of optical phenomena was examined — by invoking the principles of classical mechanics, there was some freedom of choice. And some rival hypotheses about mechanical properties of luminiferous aether were formulated. But when in 1887 — on the basis of Hertz’s experiments — Maxwell’s electrodynamics was accepted, the problem of the optics of moving bodies was transformed into the problem of electrodynamics of moving bodies. Then the freedom of choice disappeared. From the conjunction of Maxwell’s equations and Galileo’s transformations, it followed — contrary to the results of experiments — that the Earth’s motion changes the optical phenomena. The same results of experiments showed that all the phenomena under study are in perfect agreement with Maxwell’s equations in their “normal” form. In this situation, there was no choice but to preserve Maxwell’s equations and to modify Galileo’s transformations. Step by step, Lorentz, Larmor, and Poincaré inferred transformations preserving the form of Maxwell’s equations in all inertial frames of reference. Just when they finished, Einstein published exactly the same set of formulae, together with the remark that “the introduction of a »luminiferous ether« will prove to be superfluous”. It meant that Maxwell’s equations were not reducible to the laws of mechanics.